Determinants of Accounting Conservatism - Herma Wiharno; Amir Hamzah; Reza Hibar Pangestu (Faculty of Economics, Universitas Internasional Batam, 2023)
Purpose - The purpose of this research is to investigate and analyse the effects of investment opportunity set, company size, and financial distress on accounting conservatism in mining sector companies. Research Method - The research used both descriptive and verificative methods. The population of the study consisted of 34 mining sector companies that were listed on the Indonesia Stock Exchange from 2017-2019. The sample for the study included the annual reports of 39 mining sector companies listed on the Indonesia Stock Exchange during the same period. The data analysis technique used in the study was panel data regression. Findings - This research shows that Investment opportunity set has a positive and significant effect on accounting conservatism. Company size has a positive and significant effect on accounting conservatism. Financial distress has a negative and significant effect on accounting conservatism. Implication - The implication of this research is that management of mining sector companies can increase the level of accounting conservatism by considering factors such as investment opportunity set, company size, and financial distress. Additionally, the findings of this research can provide valuable information for investors, analysts, and regulators in making investment decisions in mining sector companies.